In-situ synchrotron high energy X-ray diffraction study on the deformation mechanisms of D019-α2 phase during high-temperature compression in a TiAl alloy - Xu Liu; Lin Song; Andreas Stark; Florian Pyczak; Tiebang Zhang (Journal of Materials Research and Technology)
The α2 phase with an ordered hexagonal structure has a strong mechanical anisotropy. The limited plasticity interacting with crystallographic texture formation undoubtedly complicate the deformation mechanisms of the α2 phase. Taking advantage of in-situ synchrotron high energy X-ray diffraction (HEXRD), this study unveils the origin of the α2 texture and its correlation with plastic deformation. Upon loading at 800 °C, the dislocation glide in the γ phase initiates at a stress of 370 MPa and that in the α2 phase at a stress of 670 MPa. Nevertheless, the texture evolution of the α2 phase sets in in parallel with that of the γ phase, and these textures are preliminarily established at a stress of 650 MPa. A main <11 2‾ 0> fiber texture with the c axis of the α2 unit cell aligned vertically to the compression axis has been unexpectedly evolved. This texture forms primarily via rigid body rotation and is correlated with glide and twin activation in the neighboring γ phase. The preferential orientation primarily favors double prismatic glide in α2 and in addition triggers the tensile twin activation. The grain rotation caused by the tensile twin slightly affects the α2 transverse texture evolution. The results unveil a complex interaction between the α2 phase deformability, texture evolution and the combined elastic-plastic deformation of the phases γ and α2 in TiAl alloys.